2015
DOI: 10.1039/c5cc01758k
|View full text |Cite
|
Sign up to set email alerts
|

Structural snapshots of the SCR reaction mechanism on Cu-SSZ-13

Abstract: The structure of copper sites in Cu-SSZ-13 during NH3-SCR was unravelled by a combination of novel operando X-ray spectroscopic techniques. Strong adsorption of NH3 on Cu, its reaction with weakly adsorbed NO from the gas phase, and slow re-oxidation of Cu(I) were proven. Thereby the SCR reaction mechanism is significantly different to that observed for Fe-ZSM-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(176 citation statements)
references
References 41 publications
14
162
0
Order By: Relevance
“…XANES data had earlier shown that NO and NH 3 together are able to reduce Cu 2+ to Cu + at 200 °C [8], confirming earlier findings [9,[59][60][61]. The reduction is reflected in the loss of intensity of the Cu 2+ EPR signal during the same treatment, step…”
Section: In-situ Epr Of Cu-cha In the Scr Reactionsupporting
confidence: 77%
“…XANES data had earlier shown that NO and NH 3 together are able to reduce Cu 2+ to Cu + at 200 °C [8], confirming earlier findings [9,[59][60][61]. The reduction is reflected in the loss of intensity of the Cu 2+ EPR signal during the same treatment, step…”
Section: In-situ Epr Of Cu-cha In the Scr Reactionsupporting
confidence: 77%
“…These observations indicate a Fe 3+ ↔Fe 2+ redox cycle in Fe-ZSM-5 catalysts similar as the widely accepted Cu 2+ ↔Cu + redox cycle in Cu-SSZ-13 catalysts (Figure 11a) [3,10,11,44,45,54]. More interestingly, the formed NH 4 + intermediates were found to largely determine the NH 3 -SCR activity of Fe-ZSM-5 catalysts at low temperatures ( Figure 11b).…”
Section: Zeolite Framework Typesupporting
confidence: 49%
“…Three reference spectra are given in Figure 1, showing the effect on the Cu sites of oxygen, ammonia and their combination. As discussed in more detail earlier [13], Cu is fully oxidized under oxygen flow, but becomes reduced in the presence of ammonia, as the decreased pre-edge feature (specific for Cu 2+ , 3d 9 ) confirms. The intense feature in the rising edge at 8982.7 eV is related to Cu + in linear coordination [7] and is even more pronounced without oxygen.…”
Section: Resultsmentioning
confidence: 67%
“…Gases were dosed with individual mass flow controllers to obtain a gas mixture of 0-1000 ppm NO, 0-1000 ppm NH 3 , 10% O 2 and ~1.5% H 2 O in He and analysed by an FTIR spectrometer (MKS 2030). Further experimental details are given elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation